Improving healthy eating in children: Experimental evidence - Gary Charness; Ramón Cobo-Reyes; Erik Eyster; Gabriel Katz; Ángela Sánchez; Matthias Sutter (Max Planck Institute for Research on Collective Goods, 2021)
We present a field experiment to study the effects of non-monetary incentives on healthy food choices of 282 children in elementary schools. Previous interventions have typically paid participants for healthy eating, but this often may not be feasible. We introduce a system where food items are graded based on their nutritional value, involving parents or classmates as change agents by providing them with information regarding the food choices of their children or friends. We find parents' involvement in the decision process to be particularly beneficial in boosting healthy food choices, with very strong results that persist months after the intervention.
Keywords: C93; I12; 330; Healthy eating; children; parents; non-monetary incentives; field experiment